Students’ mathematical literacy skills in solving higher-order thinking skills problems - Khaesarani, Inayah Rizki; Ananda, Rusydi (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Higher-order thinking (HOTS) problems are a learning assessment system applied to the curriculum in 2013 to improve students' higher-level thinking skills. However, teachers still familiarize students to solve problems with low-level thinking, which lower the Indonesian students’ mathematical literacy. This descriptive research with a qualitative approach aimed to explore junior high school students’ mathematical literacy skills in Kotapinang in solving HOTS problems applied to the curriculum 2013. Four students were selected as research subjects. Research instruments consisted of mathematical skills tests, literacy tests, and interviews. The researchers applied the triangulation techniques with Miles and Huberman’s model as the data analysis technique. The analysis showed that students’ mathematical literacy skills in Kotapinang were poor. The researchers recommend applying technology-based learning models, such as blended learning that is suitable for limited face-to-face learning to support the improvement of mathematics literacy skills of junior high school students in solving HOTS problems in the curriculum 2013.